Epidemiology of equine herpesvirus 2 (equine cytomegalovirus). - Browning, G F (1987)
The epidemiology of equine herpesvirus 2 was examined by using restriction endonuclease DNA fingerprints to distinguish viruses isolated from two groups of horses. The first group consisted of three yearlings isolated from other horses but in contact with each other for 418 days, whereas the second comprised seven mares and their foals, which were sampled at monthly intervals from parturition until the foals were about 180 days old. There was a complex pattern of transmission, with 15 different viruses isolated from both groups. Four distinguishable viruses were isolated from the three yearlings by day 16 of quarantine, and by day 141 an additional two viruses were isolated. Up to five different viruses were isolated from one yearling. Although four repeat isolations of one virus from the nasal cavity of one yearling over 54 days indicated that equine herpesvirus 2 established persistent infection with constant shedding, most repeat isolations yielded distinguishable viruses. Identical viruses were isolated from the nasal cavity and leukocytes of one yearling and the nasal cavity and vagina of another, indicating that a particular equine herpesvirus 2 strain was not site specific. Although seven different viruses were isolated from the three yearlings throughout the quarantine period, two appeared to establish latent infections; one virus was not isolated until 141 days after quarantine, whereas the second was first isolated 16 days after quarantine and then for the second time, from the same horse, 402 days later. Multiple concurrent local infections were demonstrated by the isolation of two or more viruses from the same nasal swab.